PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN DI PT. YAMAHA MOTOR ELECTRONICS INDONESIA - Kunto Atmojo; Atang Sudrajat (Aliansi : Jurnal Manajemen dan Bisnis, 2020)
Productivity in an organization is basically centered on the human resources owned by an organization. Given that human resources are important, attention, direction and management of human resources must be carried out and applied in the organization in order to achieve an organizational productivity goal. organizations need leaders who can direct and develop employee work performance according to the power the leader has towards achieving organizational goals. Based on the reasons above, the writer made a thesis entitled "The Influence of Leadership Style and Motivation on Employee Productivity at PT. Yamaha Motor Electronics Indonesia (Case Study at the Production Department) ”.This study aims to determine how much influence the leadership style (X1) and motivation (X2) partially on employee productivity (Y) at PT. Yamaha Motor Electronics Indonesia (Case Study in the Production Department). ”With 60 employees as respondents. The research methodology used is descriptive quantitative method. Data collection was done by using a questionnaire and tested using validity, reliability, and classical assumption tests (Normaliotas Test, Multicolonearity Test, and Auto Correlation Assumption Test, and Heteroscedasticity Test. This study resulted in three main findings in accordance with the proposed hypothesis, namely, leadership style (X1) 0.088, and motivation (X2) 0.036 had a positive and significant effect on employee productivity variables (Y) at PT. Yamaha Motor Electronics Indonesia. After conducting the research, it was concluded that the leadership style (X1) and motivation (X2) together were able to explain 73.40% of the variable (Y) while 26.60% of the variable (Y) were explained by other variables which were not studied.